Polski system podatkowy: diagnoza problemów oraz propozycja reformy - Sieroń, Arkadiusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The aim of this paper is to present the main challenges of the Polish taxation system and to propose the necessary reforms. Based on the analysis, we conclude that the three main problems of the Polish taxation system are the lack of coherent structure based on clearly defined economic principles, high tax burdens, especially on labor and capital, and its complicated and business unfriendly character. Thus — on the basis of the theory of optimal taxation — we argue that the only role of the taxation should be the fiscal function. Based on the theory and experience of other countries, we suggest also lowering the tax burden on labor and capital, and making the tax system friendlier to taxpayers. This point is crucial, since the instability and complexity of the tax law are also very important issues, although often overlooked by economists who tend to focus on the tax burden. Therefore, this paper attempts to fill this gap
Keywords: system podatkowy; zasady podatkowe; neutralność podatkowa; reforma podatkowa; podatki